Academic Breaks and Food Security Status at a Midwestern Private University - Toy, Samantha; Flores, Raymar; Kelly, Madison; De Valois, Megan; Vollmer, Rachel L. (Journal of nutrition education and behavior, 2024)
The prevalence of food insecurity on college campuses is higher than U.S. households; however it is unknown how academic breaks affect the food security status. Evaluate if breaks in the academic calendar change the food security status of undergraduate students at a Midwestern private university. This study used a repeated cross-sectional design. Two online surveys were distributed in November 2023 (the semester) and January 2024 (academic break). Eligible participants were at least 18 years old and full-time undergraduate students at a Midwestern private university. Participants completed the USDA Food Security Survey Short-Form (6-item) with a 2-item screener at both time points to measure food security. Based on a raw score, each participant was assigned a food security status (high or marginal food security, low food security, or very-low food security) during the semester and break. Differences in food security status between the semester and break were analyzed using the Wilcoxon Ranked Signs Test. Participants also answered demographic, housing, transportation, and food resource questions at each time point. Descriptive statistics were utilized to describe the study sample. A total of 57 participants completed both surveys. Most participants were female (75%), white (77%), and had financial aid to pay for tuition (98%). During the semester, 37% of the participants reported low or very-low food security in comparison to 30% during the break. There was no significant difference in students’ food security status between the semester and the break. Post hoc tests revealed a significant difference in food security status and housing during the break only [F(2,53) = 3.954, p=0.25]. Those living with a family member during the break had better food security than those living in off-campus housing. Studies with larger sample sizes should be conducted. Investigation is also needed to understand the relationship between housing during academic breaks and food security status. Bradley University Office of Sponsored Programs